(untitled) (Jurnal Destinasi Pariwisata, 2026)
Kelingking Beach in Nusa Penida is a popular tourist destination offering stunning cliff views and white sandy beaches. However, its extreme accessibility and lack of safety facilities contribute to a high risk of tourist accidents. This study aims to identify the current implementation of occupational safety and health (OHS) at the Kelingking Beach tourist attraction and formulate recommendations for a systematic and sustainable OHS implementation strategy. The research method used was a qualitative descriptive approach through in-depth interviews with Kelingking Beach managers, field officers, and tour guides, as well as field observations and documentation. The analysis was conducted using the Haddon Matrix framework to identify the causes of accidents from human factors, hazardous agents, and the environment, as well as the PDCA model and Risk Management Hierarchy to evaluate OHS. The results indicate that accidents are triggered by a combination of steep and slippery paths, a lack of safety facilities, low tourist awareness of hazard risks, and the lack of implementation of an OHS Management System (OHSMS) in accordance with ISO 31000:2009 risk management principles. In conclusion, the implementation of K3 at Kelingking Beach needs to be improved through infrastructure improvements, officer training, signage installation, and emergency evacuation SOPs to reduce accidents and improve tourist safety.